The Role of Banana Peel Surface Pores through Increasing Temperature for Efficient Hydrogen Production - Alphanoda, Abid Fahreza; Pane, Erlanda Augupta; Riyanto, Agus; Permanasari, Avita Ayu (Universitas Negeri Malang, 2024)
Porous carbon derived from banana peel has been synthesized by increasing the temperature range variation from 180 oC - 270 oC. The prepared carbon was tested in an experiment using double-chamber photoelectrochemistry to see the results of hydrogen production. SEM-EDX, FTIR, and TGA analyses identified all banana peel carbons. Optical and electrochemical properties were analyzed and measured by UV-Vis, Tauc Relationship, and Pearson Absolute Electronegativity. The amount of hydrogen gas produced from the simulation of UV-A visible light irradiation on variations of BP-240, BP-210, BP-180, and BP-Natural. The surface of BP-270 has more pores and can produce the most significant hydrogen of 1566.05 μmol·g-1. The data is compared to the weight loss percentage at a temperature of 400 oC. Generally, the degradation of the weight percentage in banana peel is up to a temperature of 900oC. This value shows that the most significant energy is needed, 1709190.45 Joules, equivalent to 1.0667 x 1025 eV. At the same time, the energy provided by UV-A is 3.099 eV, equivalent to 4.9661 x 10-19 Joule. Based on the average pores formed by the method used in this study, it explains that the temperature at BP-270 has been able to produce hydrogen in the UV-A exotherm. The increase in banana peel carbon pores increases the separation between electrons and holes and reduces the band gap distance. This study designs an efficient, cheap, and environmentally friendly photoelectrochemical system with waste materials to provide alternative energy sources by utilizing visible light energy.